PERAN MEDIA SOSIAL DALAM MENINGKATKAN PARTISIPASI POLITIK GENERASI Z DI INDONESIA - Putri, Kadek; Kertih, I Wayan; Sukadi; Widiasa, Komang; Putri, Vanya Natalia; Dwipayadnya, Made Adi Premana (Jurnal Media Komunikasi Pendidikan Pancasila dan Kewarganegaraan, 2026)
Social media plays an important role in encouraging Generation Z political participation in Indonesia, which is closely related to the advancement of digital technology, despite facing complex challenges. This research uses qualitative methods through in-depth interviews, online observations, and social media content analysis. The findings show that social media has become a significant forum for Generation Z to discuss, disseminate political information, and organize collective action. Platforms such as Twitter, Instagram, and TikTok are used as a means of communication as well as an effective mobilization tool, which encourages their involvement in social and political issues. However, obstacles such as the rise of hoaxes and polarization of public opinion also affect their understanding of political dynamics. Digital literacy is an important aspect, but there is still an inequality in access to digital literacy education among Generation Z, which has the potential to affect their participation rate. In addition, the unique characteristics of each social media platform also shape the way Generation Z interacts with political issues. Therefore, strengthening digital literacy is the main strategy so that they are able to filter information critically. Educational programs that emphasize digital literacy will help Generation Z recognize false information and understand the political context more deeply. Collaboration between governments, digital platform providers, and the wider community is needed to create a digital ecosystem conducive to healthy political participation. Thus, digital democracy in Indonesia can grow strongly, and Generation Z has a wider space to play an active role in the political process.